Trends of methicillin-resistant Staphylococcus aureus infections among Thai pediatric patients - Suchartlikitwong, Pintip; Wuthinantiwong, Nopphon; Jantarabenjakul, Watsamon; Wacharachaisurapol, Noppadol; Sophonphan, Jiratchaya; Chatsuwan, Tanittha; Puthanakit, Thanyawee (Chulalongkorn Medical Journal, 2024)
Background: Although reductions in methicillin-resistant Staphylococcus aureus (MRSA) infections have been reported, vancomycin prescription rates remain high. Objective: This study aimed to update trends in pediatric prevalence and antibiotic susceptibilities of MRSA infections. Methods: This retrospective study analyzed patients aged <15 years who contracted S. aureus infections between 2016 and 2022 at a tertiary-care hospital in Thailand. MRSA was defined as resistance to cefoxitin or oxacillin minimal inhibitory concentration of >4 µg/mL. Patients with MRSA infections and their first isolates were classified into healthcare-associated (HA) or community-associated (CA) MRSA based on surveillance definitions. Antibiotic susceptibilities were tested using the VITEK 2XL automated system and disk diffusion method. The annual prevalence of MRSA was estimated and compared using the chi-square test for trend. Results: Among 1,059 children with S. aureus infections, MRSA was identified in 82 (7.7%; 95% CI 6.2– 9.6), consisting of 65 HA-MRSA and 17 CA-MRSA infections. MRSA prevalence exhibited a significantly downward trend (P = 0.003). MRSA isolates were fully susceptible to vancomycin, linezolid, and tigecycline, with high susceptibilities to fosfomycin and fusidic acid (> 90.0%), lower to trimethoprim-sulfamethoxazole (77.0%) and tetracycline (48.0%), and the least to clindamycin (18.0%). Conclusion: A declining trend and low prevalence of MRSA infections were observed among pediatric patients, justifying the cautious use of vancomycin as empirical therapy for patients without MRSA risk. MRSA isolates remained highly susceptible to most current antibiotics, which further supports the effectiveness of these treatments against MRSA infections.